INFORMATION AVAILABLE FROM MANDATORY REPORTS AND THE POSSIBILITY OF APPLYING RANKING METHODS: THE CASE OF POLISH PUBLIC BENEFIT ORGANIZATIONS - Ewa Chojnacka-Pelowska,; Dorota Górecka, (Copernican Journal of Finance & Accounting, 2023)
The aim of this paper is to present the possibility of assessing the economic results of Public Benefit Organizations (PBOs) by using ranking methods. These methods may be used not only by individual donors, but also by local or central government bodies, that decide on subsidies. Due to the lack of unified reporting system for non- profit organizations on a global scale, the additional aim of the paper is to present mandatory reports that must be prepared by Polish PBOs. The theoretical part of the paper is the result of critical review of the law regulations in Poland and the literature in the field of non-profit reporting. The case study part of the paper is based on the example of PBOs from one of Polish voivodeships, operating in the field of ‘Sport and recreation’. In the analysis conducted an approach called MAMIMCA – Multiple Assessment Multiple Importance Multiple Criteria Analysis – was used to determine the most suitable PBOs for co-funding. In the evaluation performer nineteen different criteria were taken into account, two well-known multi-criteria decision-aiding (MCDA) techniques were used (PROMETHEE II and TOPSIS) and two various vectors of weights were applied. As a result, the ranking of ten selected PBOs was received allowing to obtain a comprehensive picture of entities considered.